Monitoring the Soil Water Content Using Time Domain Reflectometry in a Clay Loam and an Organic Soil - Hasan Sabri Özturk; Roger Hartmann (Journal of Agricultural Sciences)
n the present study, Time Domain Reflectometry TDR and tensiometers were used to follow changes in soil water content and soil water pressure head over time in soil containers filled with a clay loam soil and an organic soil. The moisture content changes throughout the soil columns were determined by three-rod TDR probes and tensiometers inserted at the depths of 5, 15, 25, 35 and 45 cm. In the experiment, changes in soil water content and soil water pressure head were determined during and after the simulation of 15 L demineralized water applied at a constant rate of 20 mm hr-1 . The water movement through the clay loam soil was initially fast and the first moisture content change at the depth of 15 cm was detected during the first half an hour but later slow water movement was observed. For the organic soil, change in the moisture content with depth was slow compared with that of the clay loam soil. The first change in moisture content at the depth of 15 cm was observed after only 1 hour from the simulation of water. The highest moisture level, 48.6%, at the depth of 5 cm was determined only after approximately 2.5 hours later from the beginning of simulated rainfall.